The second village seminar research in Átány (2022) - Nagyné Molnár, Melinda (ACTA REGIONIS RURUM, 2023)
The Village Seminar Research Workshop, which has been conducting research since 2007, visited Átány in 2014 as the seventh place in the selection of its nine sample sites. In 2016, the first "deep drillings" were completed at the selected locations of our village research. We started returning to our previous locations in 2017. This is of great importance because the return makes it possible to monitor trends, i.e. to be able to follow the social and economic changes of the space over time. We consider it important and desirable that the investigation at a specific location is not a one-time occasion, but a continuous process. We also returned to Átány in 2022.
Keywords: monitor trends; village research; Átány